(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to determine the best fermentation time to obtain pineapple skin probiotic drinks and to determine the effect of fermentation time on the chemical, microbiological and organoleptic characteristics of pineapple skin probiotic drinks. This research method used a simple one-factor Completely Randomized Design consisting of 5 treatments and 3 replications so as to obtain 15 experimental units. The treatment consisted of 5 treatments, namely the duration of fermentation 24 hours, 48 hours, 72 hours, 96 hours, 120 hours. Parameters observed include chemical and microbiological properties, namely pH, vitamin C, ash content, lactic acid, total lactic acid bacteria, while for organoleptic properties include aroma, color and taste. Making a probiotic drink based on bogor pineapple skin using lactobacillus casei with different fermentation times has a significant effect on the parameters of pH, lactic acid, total lactic acid bacteria and has a significant effect on color organoleptic parameters. While the parameters of vitamin C, ash content, aroma and taste did not have a significant effect. Making a probiotic drink based on bogor pineapple skin using lactobacillus casei with different fermentation times, the best is in the 24-hour fermentation treatment.